Linking Coleopteran Diversity With Agricultural Management of Maize-Based Agroecosystems in Oaxaca, Mexico - González González, Cecilia; Lara García, Tania; Jardón-Barbolla, Lev; Benítez, Mariana (Frontiers in Sustainable Food Systems, 2020)
Biodiversity is known to be influenced by agricultural practices in many ways. However, it is necessary to understand how this relation takes place in particular agroecosystems, sociocultural contexts and for specific biological groups, especially in highly biodiverse places. Also, in order to systematically study and track how biodiversity responds or changes with agricultural practices, it is necessary to find groups that can be used as practical indicators. We conduct a study of beetle (Coleoptera) diversity in maize-based agricultural plots with heterogeneous management practices in the Central Valleys of Oaxaca, Mexico, a region with outstanding biodiversity and a long agricultural history. We use a mixture of local knowledge and multivariate statistics to group the plots into two broad and contrasting management categories (traditional vs. industrialized). Then, we present an analysis of Coleopteran diversity for each category, showing higher levels across different diversity indexes for the traditional plots. Specifically, Coleopteran guilds associated with natural pest control and soil conservation are more common in traditional plots than in industrialized ones, while herbivorous beetles are more abundant in the second. Also, our results let us postulate the Curculionidae family as an indicator of both management type and overall Coleopteran diversity in the agricultural lands of the study site. We discuss our results in terms of the agricultural matrix quality and its role in strategies that favor the coexistence of culturally meaningful agricultural systems and local biodiversity.